'This time I'm (not) voting': A comprehensive overview of campaign factors influencing turnout at European Parliament elections. (December 2020) - Marquart, Franziska; Goldberg, Andreas C; de Vreese, Claes H
Research has investigated numerous factors influencing turnout for European Parliament elections but paid insufficient attention to the role of campaign influences. Using survey data collected in the context of the 2019 European Parliament elections, we assess citizens' passive exposure to media coverage and political advertisements, active forms of engagement such as visiting a party's website and interpersonal communication on- and offline. We test to which extent these activities contribute to the likelihood that citizens vote. Our study highlights the importance of information factors beyond well-established turnout determinants. The results confirm the mobilizing influence of a number of variables, but we also find consistent negative effects of online forms of communication and engagement. We discuss these findings with regard to a potentially 'toxic' online information environment.